Annulation of Indoles with 1,n-Dibromoalkanes by a Pd(II)-Catalyzed and Norbornene-Mediated Reaction Cascade - Henkel, Michael; Bach, Thorsten (Synthesis, 2020)
Employing 1,3-dibromopropane, 1,4-dibromobutane, and 1,5-dibromopentane as biselectrophiles, the annulation of indoles was probed in the presence of PdCl2(MeCN)2 as a catalyst and norbornene as a transpositional ligand. Ring formation to a five-membered ring was observed at positions C2 and N, while annulation of a six-membered ring occurred at positions C2 and C3. The latter cascade process was successfully applied to the direct synthesis of 1,2,3,4-tetrahydrocarbazoles from indoles (11 examples, 31–68% yield). Seven-membered-ring annulation was feasible by an initial coupling at positon C2 followed by alkylation at C3.
Keywords: alkylation; C–H activation; domino reaction; indoles; Pd catalysis